Simulasi Data Gempa Bumi Berbasis 3 Dimensi - Barasia Dwi Putra; Beny YV Nasution (Informatics Engineering Department-UWKS, 2021)
Earthquake is a frequent event in the earth 's crust, the cause is shifting tectonic plates. While the Indonesian region is between 3 plates of the earth, consequently almost all parts of Indonesia damaged, especially in earthquake-prone zones . One way to reduce the impact is to build a system modeling [ 7 ] tested with simulation results of the model of permanent buildings that collapsed 1 bar and 15 bar (4 columns), but for building models Knockdown no collapse . However , research has not yet been proven to be known computerized data accuracy earthquake used for testin. Therefore , innovation arises earthquake simulation techniques appropriate seismic data previously [ 7 ] that the frequency of 0.25 Hz to 2 Hz into the form of 3 dimensions in order to know the type of an earthquake according earthquake data used . In this study used the object in the form of 4 pieces of the cube as a reference to compare the seismic movement at each frequency and 2 testing with different amount of RAM that is 160 Mb and 1.00 Gb . The results obtained from these simulations to test 2 is the display frequency information that is 0.25 Hz , 0.5 Hz , 1.5 Hz , 2 Hz and a duration of 15 seconds and the number of seismic movements amounted to 3.5 times , 7.5 times , 22.5 times , 30 times